Damage detection in composite plate based on vibration Measurements using Genetic Algorithm - Abdulhussein, Rafal Taha; M., Muhammad A. (Al-Nahrain Journal for Engineering Sciences, 2017)
The effect of defect on structures and machines has negative consequences on them and it always takes researchers concern and attention in order to find feasible solutions to trace and detect the location of the defect accurately.In this research, the effect of a hole with different diameters on a square composite plate is studied as well as the effects of both the boundary condition and the plate thickness, furthermore, Vibration analysis of composite plate has been studied numerically and experimentally. The Numerical analysis has been carried out by using FEM by building MATLAB program as well as (ANSYS 15). The experimental part of this research is done by using vibration measuring instruments. The rate of error among the experimental tests and the numerical solution is less than 15%. These results have been used an inputs to the Genetic Algorithm model that the defect is located by, with a high percentage of success.